Motivações, riscos e benefícios na terceirização de sistemas de informação: confrontando as visões de provedores e de contrastantes de serviços em Maceió - Lins, Matheus Icaro Agra; Duda Jr., José da Silva; da Cunha, Mônica Ximenes C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Information Systems Outsourcing has become a strategy often sought by organizations in recent years. Numerous studies found in literature mainly deal with aspects of this phenomenon in the private sector. In face of the scarcity of studies directed to the public sector, this paper aimed to identify the motivations, risks and benefits of information systems outsourcing within the scope of a public-private partnership, confronting the views of providers and contractors. The research method was quantitative and used the survey method to collect data applying two questionnaires, one for the providers and another for the contractors. Then, a statistical data analysis was performed to describe a comparison between both views. In this way, it was possible to identify and verify the differences between motivation, risk and benefit indicators of a public-private partnership in the views of IT services suppliers and contractors. Twenty-nine public organizations in the state of Alagoas and fifteen IT service providers participated in the survey. Results indicate that, when comparing both views, some divergences can be highlighted, such as the cost-reduction motivational factor. However, both sides agree that the scarcity of human and technological internal resources is a key factor to make a public organization turn to an external supplier. For public organizations, excessive reliance on suppliers proved to be the most worrisome risk factor. For outsourcers, the most important threat was political pressure.